Functionality of lower limb with exposed bone using VAC® negative pressure wound therapy vs. medial calf flap - Chau Ramos, Enrique Antonio (2023)
Objective: To compare two reconstructive surgery techniques for lower limb injury with exposed bone and demonstratethat the VAC® (vacuum-assisted closure) negative pressure wound therapy is an alternative for potential recovery showingno significant changes that could lead to functional compromise. Materials and methods: An analytical, prospective, quantitative and longitudinal study conducted with all the patientsof Clínica Stella Maris with traumatic injuries of the lower limb and exposure of the middle third of the tibia treated withthe VAC® system and the medial calf flap in 2019. Results: The measurement obtained with the functional ambulation categories (FAC) scale showed better resultsamong the patients treated with the VAC® technique (since 50 % got grade V) than those who underwent the flaptechnique (50 % got grade IV), being the differences statistically significant (p < 0.05). It was observed that the time to closure was longer with the VAC® technique due to the progressive regeneration process consisting of the complete filling or coverage of the lesion area. On the other hand, the difference in the postoperative pain intensity between the two techniques was evident, being moderate to intense with the flap technique and mild, for the most part, with the VAC® technique. Conclusions: The VAC® suction system is effective for bone coverage in traumatic defects of the anterior middle third of the tibia. It is an alternative for potential recovery that does not change the anatomical structures because it provides better functional results and fewer complications. It is a useful and safe option that stimulates wound closure andminimizes the need for surgical treatment.